Pengaruh Audit Tenure, Ukuran Perusahaan, Ukuran Kap, Umur Perusahaan Terhadap Audit Delay Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015- 2019 - Rizky Yanuar Christianta Tarigan; Wenny Anggresia Ginting; Yulia Theresia Tambunan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Becoming a public company is one of the way for a company to survive of business competition. Especially mining companies that we know that not a little capital is needed in developing their business. Therefore, it is very important for mining companies to pay attention to delays in the publication of audited financial statements for attract investors. In this study, the multiple linear method using outlier transform is used by the researcher. So that this study conclude that audit tenure and company size has no effect on audit delay. KAP size and company age leaven a negative effect on audit delay. Keywords: Audit Delay, Audit Tenure, Company Size, KAP Size, Company Age